Komunikasi Ritual Dalam Tradisi Lokal Membaca Lontar (Memaos) Sebagai Media Untuk Melestarikan Budaya Masyarakat Adat Di NTB - Miharja, Dian Lestari; Karyadi, Wirasepta; Sutarini, Ida Ayu; Paramita, Eka Putri (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
The tradition of memaos lontar (reading lontar) in West Nusa Tenggara (NTB) is a cultural heritage preserved by indigenous communities for generations. This tradition aims to safeguard culture through chanted lontar manuscripts, which contain valuable information about various aspects of life. A significant challenge is the language complexity, which is difficult for those without direct lineage to the manuscript's authors. However, periodic memaos activities provide a solution to this issue while fostering interactions as a form of ritual communication. This perspective highlights that ritual communication plays a role in creating, transforming, and replacing shared culture. A qualitative descriptive study with FGD revealed two main findings: (1) ritual communication in the memaos tradition encompasses dimensions of process, meaning, and communication patterns; and (2) efforts to preserve the tradition include successor regeneration and group communication to enhance interaction among pepaos.